Long Non-Coding RNA and mRNA Profiling in Early-Stage Bovine Embryos Treated with Glutathione - Qinqin Guo; Lixin Cui; Weijun Sun; Feng Li; Haisheng Hao; Xueming Zhao; Huabin Zhu; Weihua Du (MDPI AG, 2020)
We measured differential expression profiles of genes and long non-coding RNA (lncRNA) using RNA sequencing in bovine embryos with or without glutathione (GSH) treatment. Bovine embryos fertilized in vitro were treated with GSH to blastocyst. Embryos at the 8-16-cell and morula stages were collected, with embryos without GSH treatment as the control. RNA was isolated, amplified, and sequenced. Differentially expressed genes (DEGs) and lncRNAs (DElncRNAs) were identified and bioinformatic analyses carried out. Transcript levels were confirmed using quantitative RT-PCR. A total of 4100 DEGs were identified, of which 3952 were in GSH-treated morulae and 884 in untreated morulae. More gene ontology (GO) terms were associated with GSH treatment than with control conditions. KEGG analysis showed that glutathione metabolism, citrate cycle, and metabolic pathways involving glycine, serine, and threonine were observed only in GSH-treated embryos. Among 4273 DElncRNAs identified, 59 were potentially important in GSH-treated embryo development, including 14 involved in glutathione metabolism. The 59 DElncRNAs co-expressed with protein-coding mRNAs involved similar GO terms and pathways as the DEGs. This appears to be the first comprehensive profiling of DEGs and DElncRNAs in bovine embryos fertilized in vitro with or without GSH, and the first systematic screen of potential lncRNAs in bovine embryos.